Familia y sociedad en un concejo marítimo del noroeste peninsular: el municipio asturiano de Carreño en 1753 - Suárez Álvarez, Patricia (Estudios Humanísticos. Historia, 2013)
RESUMEN: Durante el Antiguo Régimen, la geografía y climatología del Principado de Asturias hizo del mar su principal vía de comunicación. Junto con los grandes puertos de Gijón o Avilés coexistían otras poblaciones marítimas «menores» que compaginaban el aprovechamiento de los recursos que el mar les ofrecía con la agricultura. Este es el caso de la villa de Candás, capital del concejo de Carreño, que durante el siglo XVI destacó por ser un importante puerto de pesca ballenera, muy conocido en la Europa norteña. La industria de transformación de los productos piscícolas, que derivó en el siglo XIX en la creación de las fábricas conserveras, permitió al concejo cierta supervivencia autónoma respecto a las grandes entidades evitando la retracción demográfica y económica. Para aproximarnos a su historia, mostraremos «una fotografía» de un año concreto del siglo XVIII, 1752-53, y analizaremos la tipología familiar y profesional del concejo y su relación con los mecanismos económicos del territorio. ABSTRACT: The region of Asturias, situated in the north east of the Iberian Peninsula, is administratively divided into 78 counties or municipalities, with the most highly populated of these being found on the coast. During the ancien régime, the geography and climatology of Asturias meant the sea was the main connection for the region. Foods such as cereals arrived at the ports in Gijón and Avilés which allowed for the demographic development of both these cities and other «smaller» seasisde towns ahead of the rest of the region. In central Asturias, many counties combined the resources that the sea had to offer with agriculture, turning their towns into satellites for the big ports. This is the case for Candás, the capital of the county Carreño, which was recognised as an important whaling port during the 16th century and was very wellknown in northern Europe. The industry of processing fishing products, which lead to the creation of canning factories in the 19th century, allowed the county a certain autonomous survival in comparison to larger councils, avoiding both demographic and economic decline. In the mid-18th century, the Ensenada cadastre gave a population of 985 which included surgeons, notaries, various landlords, an elementary school teacher, women who kneaded bread, farmworkers and many other professions related to the fishing industry and this study is vital in understanding the sociology of the municipality. In this paper, the aim is to provide a photograph of a specific year in the 18th century, 1752-53. We analysed the county´s family structures and labour patterns in this year and how it related to the economic mechanism in the region, drawing a comparison between the main rural zones and the urban centre.